Trampas extracelulares de ADN de eosinófilos en alergias (2014)
ABSTRACT: Allergy is a hypersensitivity reaction initiated by specific immunologic mechanisms. It can be mediated by antibodies or cells, developed in individuals previously sensitized by an allergen. In most cases, the antibody responsible for the allergic reaction is immunoglobulin E (IgE). Depending on the nature and mechanism of entry of the allergen, it will bring about the production of specific IgE affecting certain organs and tissues with specific symptoms. Eosinophil extracellular DNA traps or EETs are one of the mechanisms used by eosinophils during the response phase of allergy; they have not been well studied in terms of their induction, regulation and function. EETs have been detected in inflammatory intestinal processes, autoimmune diseases and multiple infectious diseases, but few investigations have been made about their involvement in allergic diseases. This is a review about the structure of EETs, the molecules involved in their formation, and their possible role in the pathogenesis of allergies. Furthermore, the main aspects of cellular and molecular processes involved in the immunopathogenesis of allergies, and the central aspects of the structure, composition and functioning of eosinophils are reviewed.